Morphological variability in response to palaeoenvironmental change – a case study on Cretaceous ammonites. (30th April 2015) - Lehmann, Jens; von Bargen, Dieter; Engelke, Julia; Claßen, Julia
Abstract : Changes in ammonite morphology during the earliest Early Aptian (Cretaceous) of an epicontinental sea in northern Germany were investigated based on new and rich material of Deshayesites (Deshayesitidae). This is a globally distributed genus and one of the most important ammonites of the Cretaceous with respect to biostratigraphy and abundance. The purpose of our study was to describe changes in morphology over few hundred thousand years and to discuss their relationships to major palaeoenvironmental perturbations. Our material is derived from four different horizons, and the studied stratigraphical interval includes a sea‐level change, a period of warming and an oxygen depletion event. We observe variable patterns in the occurrence of different morphological groups through time, probably indicating that morphotypes were individually impacted by environmental change. These morphological groups, unequivocally attributed to Deshayesites, cannot be fit into the existing species classification system. The greatest morphological disparity in Deshayesites is multi‐causal. It may be the result of: (1) an invasion of two morphogroups new to the habitat, which thus immediately face considerably greater competition in an environment just recovered from low‐oxygen conditions in parts of the water column during an early interval within Oceanic Anoxic Event 1a (OAE 1a); or, (2) it may be due to a rise in sea level with a simultaneous invasion of competitors of Tethyan origin. This sheds new light on the current concept for high morphological variability within ammonite species and poses challenges to our current ideas about ammonite diversity and the use of well‐established index‐species in supraregional correlations.